Agronomic Behaviour and Chemical Composition of Three Varieties of Pennisetum sp in the Peruvian Tropics - Enrique Susumu Watanabe Escobedo; Ronald Juancho Ramirez; Carlos Enrique Alvarado Atanacio; Debora López Rengifo; Pedro Hugo Injante Silva; Gustavo Ampuero Trigoso; José Américo Saucedo-Uriarte (International Journal of Agronomy)
Livestock production in the Peruvian tropics is mainly based on grazing and cutting grasses, which have variable productive and nutritional characteristics according to the variety of grasses, agronomic management, and climatic conditions. The objective of this research was to compare the agronomic behaviour and chemical composition of three varieties of Pennisetum sp (Pennisetum purpureum Schum cv. Cameroon or Cameroon grass, Pennisetum sp. or Maralfalfa, and Pennisetum purpureum × Pennisetum typhoides or King grass). The experiment was carried out at the Estación Experimental Agraria “Campo Verde,” Ucayali, Peru, under a randomized complete block design (RCBD) with a 3 (Pennisetum sp. variety) × 3 (cutting age) factorial arrangement and 4 replicates each. Thirty-six subplots were installed, and treatments were randomly assigned, using vegetative seed with three buds each. Measurements of agronomic behaviour and chemical analysis were carried out in the 8th, 12th, and 16th week. The data were subjected to ANOVA and multiple comparisons with the Duncan and Kruskal–Wallis tests (p < 0.05) and correlations using Pearson coefficients (p < 0.05). The agronomic behaviour did not vary between Pennisetum sp. varieties, but according to cutting age, Cameroon grass produced greater plant height, biomass, dry matter, and Mg content at the 8th week. The highest concentrations of N (2.38 ± 0.11%), P (0.18 ± 0.01%), and Ca (0.70 ± 0.03%) were recorded at the 8th week, Zn (27.33 ± 1.91 mg/kg) at the 12th week, and Mg (0.26 ± 0.02%) at the 16th week. A negative correlation was found between biomass and the stem-leaf ratio at the 12th week because the first leaves of plants died, but the stems increased in size. It is concluded that, at an early cutting age in varieties of Pennisetum sp., lower biomass and dry matter result, but higher content of N, P, Ca, and Fe; and at a late cutting age, it shows greater biomass, dry matter, Cu, and Mg content.